Effectiveness of Single Nucleotide Polymorphism Markers in Genotyping Germplasm Collections of Coffea canephora Using KASP Assay - Akpertey, Abraham; Padi, Francis K.; Meinhardt, Lyndel; Zhang, Dapeng (Frontiers in Plant Science, 2021)
Accurate genotype identification is imperative for effective use of Coffea canephora L. germplasm to breed new varieties with tolerance or resistance to biotic and abiotic stresses (including moisture stress, pest and disease stresses due to coffee berry borer and rust), high yield and improved cup quality. The present study validated 192 published single nucleotide polymorphism (SNP) markers and selected a panel of 120 loci to examine parentage and labeling errors, genetic diversity and population structure in 400 C. canephora accessions assembled from different coffee producing countries and planted in a field genebank in Ghana. Of the 400 genotypes analyzed, both synonymous (trees with same SNP profiles but different names, 12.8%) and homonymous (trees with same name but different SNP profiles, 5.8%) mislabeling were identified. Parentage analysis showed that 33.3% of the progenies derived from controlled crossing and 0% of the progenies derived from an open pollinated bi-clonal seed garden had parentage corresponding to breeders’ records. The results suggest mislabeling of the mother trees used in seed gardens, and pollen contamination from unwanted paternal parents. After removing the duplicated accessions, Bayesian clustering analysis partitioned the 270 unique genotypes into two main populations. Analysis of molecular variance (AMOVA) showed that the between population variation accounted for 41% of the total molecular variation and the genetic divergence was highly significant (Fst = 0.256; P< 0.001). Taken together, our results demonstrate the effectiveness of using the selected SNP panel in genebank management, varietal identification, seed garden management, nursery verification and coffee bean authentication for C. canephora breeding programs.